Improvement of Reclaimed Asphalt Pavement with Crushed Rock Aggregate by Cement - Huangjing, Sirichai (Journal of Vongchavalitkul university, 2023)
Objective: To study the use of cement to improve the strength properties of reclaimed asphalt pavement with crushed rock without disposal for a guideline to reduce the process of preparing materials for road construction. Methods: The ratio of the previous studies could not be applied because some of the fine aggregate was discarded from recycled materials. Therefore, this study had to adjust the ratio of mixed material using to the size distribution standard. Then it was used to prepare unconfined compressive strength and CBR samples to determine the appropriate amount of cement by modified compaction and using the water content at the maximum dry density, added 3, 5, 7, and 9 percent cement, tested at 3, 7, 14, and 28 days of curing times. Results: Using a ratio of 1 to 3 mixed materials would optimize the mix size according to the standard criteria and used to prepare strength test samples using 6.7% water that gave the maximum dry density of 2.4 g/cm3. The non-cemented samples had an average compressive strength of 9.23 kg/cm2 and increasing cement in mix developed strength higher. The rates of increase strength curing 3-7 days will be higher than after 14 days for all cement volume ratio. Considering that at 7 days of curing, the average compressive strength was 17.63 and 25.00 kg/cm2 for cement content 3.0% and 7.5%, respectively, which was higher than the standard of the Department of Rural Roads and the Department of Highways at 17.5 and 24.5 kg/cm2. The CBR test results found that the 3% cement content sample had a CBR of 82.37%, was higher than the criteria set by both standards of 80%. The guideline to reuse of asphalt concrete surface materials without discarding materials mixed with crushed rock should be used in the ratio of 1: 3 and adding cement 3.0% and 7.5% for the strength of the material accordingly to the standards of pavement materials according to the standards set by the Department of Rural Roads and the Department of Highways, respectively.